2014
DOI: 10.1136/sextrans-2014-051537
|View full text |Cite
|
Sign up to set email alerts
|

HPTN 035 phase II/IIb randomised safety and effectiveness study of the vaginal microbicides BufferGel and 0.5% PRO 2000 for the prevention of sexually transmitted infections in women

Abstract: Objectives To estimate the effectiveness of candidate microbicides BufferGel and 0.5% PRO 2000 Gel (P) (PRO 2000) for prevention of non-ulcerative sexually transmitted infections (STIs). Methods Between 2005 and 2007, 3099 women were enrolled in HIV Prevention Trials Network (HPTN) protocol 035, a phase II/IIb evaluation of the safety and effectiveness of BufferGel and PRO 2000 for prevention of sexually transmitted infections, including Neisseria gonorrhoeae (GC), Chlamydia trachomatis (CT), and Trichomonas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 24 publications
0
18
2
2
Order By: Relevance
“…only1[57]2[69,78]3Regional lang. & English17[40,41,43,44,4749,53,54,56,5962,7375]7[40,41,70,76,77,79,80]22 b  Not stated11[42,45,5052,55,58,6366]5[46,67,68,71,72]16AI – anal intercourse, VI – vaginal intercourse, UAI – unprotected anal intercourse, UVI – unprotected vaginal intercourse, F – female, M – male, Mix – data available on mixed gender only, FSW – female sex worker, MSM – men who have sex with men, shebeen – an informal establishment serving alcohol, STI – sexually transmitted infection, VCT – voluntary counselling and testing, ACASI – audio computer-assisted self-interview, FTFI – face-to-face interview, SAQ – self-administered questionnaire, CRS – cluster random sample, SRS – simple random sample, RDS – respondent-driven sample, RCT – randomized controlled trial a Studies which reported AI prevalence for unprotected AI only. b Sum lower than expected as two studies report on both higher and general-risk populations. c Recall period referred to here as “general” when participants were asked “Do you practise anal sex”, or similar. d Defined by author as “high risk” but no definition provided; sample consists of 79% FSW [70]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…only1[57]2[69,78]3Regional lang. & English17[40,41,43,44,4749,53,54,56,5962,7375]7[40,41,70,76,77,79,80]22 b  Not stated11[42,45,5052,55,58,6366]5[46,67,68,71,72]16AI – anal intercourse, VI – vaginal intercourse, UAI – unprotected anal intercourse, UVI – unprotected vaginal intercourse, F – female, M – male, Mix – data available on mixed gender only, FSW – female sex worker, MSM – men who have sex with men, shebeen – an informal establishment serving alcohol, STI – sexually transmitted infection, VCT – voluntary counselling and testing, ACASI – audio computer-assisted self-interview, FTFI – face-to-face interview, SAQ – self-administered questionnaire, CRS – cluster random sample, SRS – simple random sample, RDS – respondent-driven sample, RCT – randomized controlled trial a Studies which reported AI prevalence for unprotected AI only. b Sum lower than expected as two studies report on both higher and general-risk populations. c Recall period referred to here as “general” when participants were asked “Do you practise anal sex”, or similar. d Defined by author as “high risk” but no definition provided; sample consists of 79% FSW [70]. …”
Section: Resultsmentioning
confidence: 99%
“…The two highest AI prevalence estimates were reported by male school pupils (61.7% and 70.0%) in studies using ACASI [46] and a mixture of ACASI and SAQ [49]. In contrast, the lowest estimates (≤3% over various recall periods) were reported by adult women in FTFI [42,47,5052,59,65](Figure 1a). Apart from one estimate [81], AI prevalence among higher-risk respondents was consistently high across recall periods (28.4–42.8%) (Figure 1b) and generally higher than for general-risk populations.…”
Section: Resultsmentioning
confidence: 99%
“…The HPTN 035 phase II/IIB safety and efficacy study of vaginal microbicides recently evaluated BufferGel and 0.5% PRO 2000 for prevention of T. vaginalis, C. trachomatis and N. gonorrhoeae. Regrettably, neither candidate microbicide had any protective effect against trichomoniasis, chlamydia, or gonorrhea [42]. …”
Section: Trichomonas Vaginalis: Curable But Not Under Controlmentioning
confidence: 99%
“…Також досліджувалися вагінальні мікробіциди, такі як BufferGel і 0,5 % PRO 2000, для профілактики інфікування Trichomonas vaginalis, Chlamydia trachomatis, Neisseria gonorrhoeae. На жаль, жоден з кандидатів цих бактерицидних субстанцій не мав достатнього захисного ефекту проти трихомонозу, хламідіозу або гонореї [11]. Відсутність підходящих тварин-моделей для вивчення патогенезу трихомонадної інвазії ускладнювала проведення стандартних досліджень з метою випробовування мікробіцидів.…”
Section: (95)2019 інфекційні хворобиunclassified